QUANTITATIVE VERIFICATION OF UNTRADITIONAL DIAGNOS-TICS METHODS - Zakharov, I. G.; Tyrnov, O.F. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The task of quantitative verification of untraditional diagnostics methods that use simple indexes (colour and nail form,  structure peculiarity of eye iris and etc.) is formulated. The nail lunulae length as a simple index was used to accomplish the task. The conclusion of diagnostic meaningfulness of simple indices is drawn. The nonrandom nature of weekly rhythm in change of nails lunulae length is shown, the presence of weekly rhythm of human functional asymmetry is determined.  The present approach allows, in principle, to study other methods of untraditional diagnostics and can be used as an independent research method of organism functioning peculiarities that require long-term regular measuring.